20 The role of specialist nurses within a paediatric inherited cardiovascular disease service. (2nd February 2018) - Field, E; Callaghan, N; Walsh, H; Lord, E; Hudson, ME; Jones, S; Kaski, JP
Abstract : Purpose: The management of inherited cardiovascular diseases (ICVDs) can present significant challenges. Increased risk of sudden cardiac death, lifestyle limitations and considerations around inheritance risk are among the key concerns for families. An audit was conducted within a busy paediatric ICVD service to understand the contribution of specialist nurses in supporting this patient group. Methods: Timesheets were distributed to five specialist nurses and these were completed over a two week period. Nurses were asked to record the time spent undertaking each activity during their working day and to classify activities into categories for ease of analysis. Results: A total of 276.9 working hours were recorded. The largest proportion of time (17.2%) was spent on preparing clinics. This included calling families in advance of appointments to provide information and advice, gathering relevant clinical information regarding family members and organising appropriate clinical tests. 6% of time was spent giving clinical advice in face-to-face nurse consultations. Compilation of family health histories accounted for 5.4% of time. Other activities taking up significant time included liaison with other medical teams (both internal and external), creation of new information leaflets and patient care pathways, responding to clinical queries and liaising with schools. Conclusion: Specialist nurses within an ICVD service provide multifaceted care which requires relevant experience, expert knowledge and a range of interpersonal skills. Nurses advocate for patients and ensure holistic care by providing a vital link between multi-disciplinary team members. Specialist nurses are ideally placed to optimise the management of patients affected by this group of conditions.